TEACHING CHILDREN TO MAKE CREATIVE MODELS FROM DIFFERENT PLANTS - Raxmatova Ikbolxon Inomjonovna; Tojiyeva Marjona Yuzboyevna (Journal of new century innovations, 2022)
Annotation: In this article, we will teach children to make creative models from various plants, to develop an aesthetic attitude to things and events in nature, to teach children to be able to feel and understand the beauty in them, and to apply these feelings and concepts to life. issues of developing aesthetic and emotional sensitivity to nature, regularly and purposefully developing perception, color perception, composite culture, spatial thinking, fantasy, visual imagination and combination, solving creative tasks into clear images illuminated.